Analisis Laporan Arus Kas Sebagai Alat Ukur Efektivitas Kinerja Keuangan Pemerintah Kota Magelang Tahun 2018-2021 - Dwi Nurrahmawati; Erni Agustin; Risma Wira Bharata (Universitas 17 Agustus 1945 Semarang, 2023)
The purpose of this study was to determine the growth of cash flows and the effectiveness of using cash flow reports as an indicator of the financial performance of the Magelang city government in 2018-2021. This study uses a quantitative descriptive method based on secondary data, namely the cash flow report of the Magelang city government. The data was taken through the official website of the Magelang City government. Based on this research, it can be seen that the overall cash flow growth in 2018-2021 for operating, investment, financing and transitory activities indicates a fairly good financial performance from the Magelang city government. In addition, relatively high free cash flow indicates that the Magelang city government has cash left that can be used for various activities to support high-quality public services